(untitled) (Annals of Medical Research, 2021)
Aim: Thyroid disorders have a crucial impact on maternal and fetal health During pregnancy, there are different results regarding the relationship between thyroid disorders, insulin resistance (IR) and vitamin D levels in different studies.We aimed to investigate the association between thyroid hormone levels and IR and vitamin D levels in pregnant women. Material and Methods: In this study, a total of 187 pregnant women between 5-39 gestational weeks consisting of 101 patients with altered TSH and free T4 (FT4) levels, and 86 patients with normal TSH and FT4 levels, were enrolled in four months period. Their TSH, FT4, Anti TG, Anti TPO,25-hydroxy vitamin D, insulin, glucose,creatinine,hemoglobin levels and age, gravidea, gestational week and insulin resistance (IR) were defined. Statistical methods were used for analyses. Results: In the group with thyroid hormone alterations, FT4 (p=0.010), creatinine (p=0.001) and glucose (p=0.044) levels were significantly higher.Pregnancy week was significantly earlier in the hyperthyroidism group (p=0.001). Vitamin D levels were not associated with BMI, TSH, FT4, anti TG and anti TPO. Although not significant TSH, anti TPO and vitamin D mean levels were higher in patients who had IR .Those with positive anti-TG and anti-TPO and presence of IR were higher in the study group. Conclusion: In our study, levels of vitamin D and thyroid hormones were not associated; anti TG and anti TPO levels and higher IR presence were observed in pregnant women with altered thyroid hormone levels. During the early gestational weeks, patients should closely be monitored for hyperthyroidism and hypothyroidism as well as insulin resistance for detecting DM throughout the trimesters of gestational period.